2017
DOI: 10.1039/c6ra27750k
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of hot spots in large scale fluidized bed reactors

Abstract: The influence of gas velocity and bed diameter on temperature and hot spot profile in gas-solid fluidized beds is studied based on a 2D pseudo homogeneous phase model. A dimensionless number, the fluidized Prater number b f , is introduced into fluidized bed reactors to estimate the temperature gradient and hot spot profile based on various operating parameters and a quantitative relationship is established.Contrary to fixed beds, in fluidized beds, with low gas velocity and small bed diameter, there tend to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…27 Clarke claimed that coke is mainly formed from CH 3 Cl cracking on copper, e.g., 2Cu + 2CH 3 Cl → 2CuCl + CH 4 + H 2 + C. 29 Wessel et al reported an enhanced coke deposition at higher reaction temperatures. 30 It has also been reported that insufficient fluidization in the reactor may lead to the formation of localized hot spots, 31 up to 1000 °C during the industrial direct synthesis, thereby facilitating thermal cracking of CH 3 Cl. The deposited coke may contain chlorine, in which case it has been found to further catalyze the cracking process at lower temperatures, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…27 Clarke claimed that coke is mainly formed from CH 3 Cl cracking on copper, e.g., 2Cu + 2CH 3 Cl → 2CuCl + CH 4 + H 2 + C. 29 Wessel et al reported an enhanced coke deposition at higher reaction temperatures. 30 It has also been reported that insufficient fluidization in the reactor may lead to the formation of localized hot spots, 31 up to 1000 °C during the industrial direct synthesis, thereby facilitating thermal cracking of CH 3 Cl. The deposited coke may contain chlorine, in which case it has been found to further catalyze the cracking process at lower temperatures, i.e.…”
Section: Introductionmentioning
confidence: 99%